Fasting breath H(2) and gut microbiota metabolic potential are associated with the response to a fermented milk product in irritable bowel syndrome - Le Nevé, Boris (PLoS One, 2019)
OBJECTIVES: Aim of this study was to assess the effect of a fermented milk product containing Bifidobacterium lactis CNCM I-2494 (FMP) on gastrointestinal (GI) symptoms and exhaled H(2) and CH(4) during a nutrient and lactulose challenge in patients with irritable bowel syndrome (IBS). METHODS: We included 125 patients with IBS (Rome III). Fasted subjects were served a 400ml liquid test meal containing 25g lactulose. The intensity of eight GI symptoms and the amount of exhaled H(2) and CH(4) were assessed before and during 4h after meal intake. The challenge was repeated after 14 days consumption of FMP or a control product in a double-blind, randomized, parallel design. The metabolic potential of fecal microbiota was profiled using 16S MiSeq analysis of samples obtained before and after the intervention. RESULTS: 106 patients with IBS were randomized. No difference between FMP or control groups was found on GI symptoms or breath H(2) and CH(4) in the whole cohort. A post-hoc analysis in patients stratified according to their fasting H(2) levels showed that in high H(2) producers (fasting H(2) level≥10ppm, n = 35), FMP consumption reduced fasting H(2) levels (p = 0.003) and H(2) production during the challenge (p = 0.002) and tended to decrease GI discomfort (p = 0.05) vs. control product. The Prevotella/Bacteroides metabolic potential at baseline was higher in high H(2) producers (p<0.05) vs. low H(2) producers and FMP consumption reduced this ratio (p<0.05) vs. control product. CONCLUSIONS: The response to a fermented milk product containing Bifidobacterium lactis CNCM I-2494 (FMP) in patients with IBS seems to be associated with the metabolic potential of the gut microbiota. TRIAL REGISTRATION: ClinicalTrial.gov NCT01252550. These results were presented as congress posters at Digestive Disease Week 2016 in San Diego, USA and United European Gastroenterology Week 2016 in Vienna, Austria.